PERLINDUNGAN HUKUM ISLAM TERHADAP JANIN - Idrus, Achmad Musyahid (Al-Daulah : Journal of Criminal Law and State Administration Law, 2015)
Janin or fetus is one of the real problem in Islamic law sincelong time ago till today. There are many problems that caused janin or fetus aborsed by mothers and the most important of this  problems  is  the  unpragnancy.  Islamic  law  stressed  that janin or fetus must be respected by all humans so that Islamic law encouranges mothers and father to  protect the janin or fetus in their mother’s uterus. That why, janin or fetus actually has life  and  has potentially to grow up  in  many cells to be human.